Kompetensi Guru Agama Hindu Yang Belum Bersertifikat Pendidik - I Made Wiguna Yasa; I Komang Wisnu Budi Wijaya (Purwadita : Jurnal Agama dan Budaya, 2020)
This research aims to describe the competence of Hinduism teachers at the Elementary Schools level in Penebel sub-district who do not have educator certificate. This research is classified into qualitative research. The method that used is a survey method. The population of this research were Hinduism teachers at Elementary Schools level in Penebel sub-district who do not have educator certificate. The sampling technique that used is saturated sampling technique. The research instrument used was a teacher competency questionnaire. The teacher competency data analysis was conducted descriptively. The results of this research stated that the competence of Hinduism teachers at the Elementary Schools level in Penebel sub-district who do not have educator certificate was classified as high (average score 73.00). Keywords: Competence; Hinduism Teacher; Elementary School; do not have Educator Certificate